Student's Experiences on Learning Therapeutic Relationship: A Narrative Inquiry. Issue 1 (March 2021) - Zou, Ping; Luo, Yan; Krolak, Kathren; Hu, Jiale; Liu, Lichun W.; Lin, Yanxia; Sun, Winnie
Despite the importance of the therapeutic relationship on nursing practice, the literature regarding teaching and learning therapeutic relationship is limited. This paper discussed how an undergraduate nursing student learned therapeutic relationship in an acute care setting. Narrative inquiry was applied as a research methodology. The student's reflection served as the narrative in this paper. Collaboratively, researchers conducted data analysis, common themes were drawn, and a summative narrative was presented. Based on the student's narrative, a three-dimensional model, including practical knowledge, theory, and reflection, has been created as our summative narrative. This model suggests that, to facilitate a learning process on creating therapeutic nurse–patient relationship, practical knowledge is the foundation, theory is a leading guide, and constant reflection is a learning tool which transforms learning into a reflective and meaningful experience. To promote learning on therapeutic relationship, nurse educators should emphasize the importance of both practical knowledge and theory. Constant reflection as a learning tool should be encouraged and embedded in nursing curriculum. Diverse approaches of reflection should be promoted.